Power electronic buck chopper / Sharul Azlan Sungit - Sungit, Sharul Azlan (2006)
This thesis presents the implementation of the dc buck converter for trainer applications. The design is based on Peripheral Interface Controller field programmable that acts as a controller. The output voltage is controlled using well-known Pulse Width Modulation (PWM) technique. With continuous input and output current, wide output voltage range and small output filter, Buck topology has gathered more and more attention in recent years. Soft switching is especially important to a buck converter because the power handling capability requirements of semiconductor devices are higher than those of other topologies. Satisfactory agreement between simulated and laboratory results were observed